HTA Training for Healthcare Professionals: International Overview of Initiatives Provided by HTA Agencies and Organizations - Hoxhaj, Ilda; Castagna, Carolina; Calabrò, Giovanna Elisa; Boccia, Stefania (Frontiers in Public Health, 2022)
Background Health Technology Assessment (HTA) is a multidisciplinary process that uses rigorous methods to determine the value of health technologies and to steer decision-making in order to promote an equitable, efficient, and high-quality health system. Given the integration of technological innovation into clinical practice, healthcare professionals are required to properly know and assess technologies and use evidence-based approaches such as HTA. Therefore, the implementation of education and training in HTA is needed. The aim of this study was to investigate the state of the art of HTA training for healthcare professionals and to map the existing training initiatives in HTA provided by international HTA agencies and organizations all over the world for this target population. Methods The websites of member agencies of EUnetHTA, INAHTA and HTAi were explored from March to November 2020 for identifying the training initiatives in HTA for healthcare professionals. Specific keywords were searched in English and adapted to French, Portuguese, Spanish, Italian and German. Data extraction of the retrieved training initiatives was conducted from November 2020 to February 2021 and considered: agency, country, website, coordinator, type of initiative, target, topic, main contents and language. Results Out of 124 agencies screened, only 18 provided training initiatives for healthcare professionals. A total of 55 training initiatives were analyzed, 85.5% of which were delivered at the European level and 14.5% by international agencies. The countries with a greater number of courses were: Austria, Argentina, Spain, Portugal, and the United Kingdom. Twenty-one training initiatives focused on HTA application and methodology while 34 on specific HTA domains, particularly on the economic one. The technologies covered were mainly drugs. Conclusions A paucity of focused training programs in HTA for healthcare professionals was revealed by the study. HTA allows to bridge the gap between scientific evidence and policy decision-making. Indeed, education of health professionals in this field should be a key driver for increasing the correct use of HTA, as an applicable tool for health governance and keeping up with technological innovations. Thus, capacity building of health professionals in this area should be boosted by using proper and effective initiatives and strategies.